1984
DOI: 10.1139/z84-043
|View full text |Cite
|
Sign up to set email alerts
|

Copulatory plugs in Richardson's ground squirrels

Abstract: The frequency with which copulatory plugs, coagulated ejaculate located in the vaginae of recently inseminated females, occur in Richardson's ground squirrels was determined during a 4-year study. In each year, on average, 37% of females captured on 3 consecutive days centered on the time of mating had a copulatory plug. Plugs filled the vaginal lumen, firmly adhered to the vaginal wall, sometimes remained in place as long as 15 – 17 h, and were expelled via sloughing of the vaginal epithelium. The function(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Brachyteles), an Old World monkey (M. arctoides), and in chimpanzees, so their occurrence is not limited by phylogenetic factors. The hypothesized functions for plugs include assisting sperm retention within the female's reproductive tract [30], and blocking access to the os cervix by gametes of rival males [28]. Likewise, although complex variations in the biochemical makeup of seminal vesicular and prostatic secretions have been described in primates and other mammals [12,13,16] we still know relatively little about their functional significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachyteles), an Old World monkey (M. arctoides), and in chimpanzees, so their occurrence is not limited by phylogenetic factors. The hypothesized functions for plugs include assisting sperm retention within the female's reproductive tract [30], and blocking access to the os cervix by gametes of rival males [28]. Likewise, although complex variations in the biochemical makeup of seminal vesicular and prostatic secretions have been described in primates and other mammals [12,13,16] we still know relatively little about their functional significance.…”
Section: Discussionmentioning
confidence: 99%
“…In some arthropods and snakes, for example, copulatory plugs may act as physical barriers, sealing the entrance to the female's reproductive tract, and preventing subsequent matings [1,26,27]. This 'chastity belt' hypothesis has also been mooted for mammals [28] but has not been confirmed [29,30]. However, it is possible that mammalian copulatory plugs might function to minimize loss of sperm from the female's reproductive tract, as has been shown to be the case in the rat [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Because females tend to show natal philopatry, however, neighbours tend to be related by maternal descent (Michener 198 1, 1983a). Further, neighbouring individuals would be likely to share genes via paternal descent given multiple mating by males (Michener & Koeppll985;Michener 1983b;Van Staaden et al 1994;Michener & Mclean 1996). Thus, beneficent behaviour would tend to be directed toward relatives as would be predicted where kin selection has played a role in the evolutionary appearance or maintenance of sociality (Michener 19831).…”
Section: Discussionmentioning
confidence: 99%
“…Male tammar wallabies attempt to reduce the chance of sperm competition by various mechanisms, including extensive pre-and postcopulatory mate guarding behaviour with frequent mating (Ewen et al 1993, Rudd 1994, Rudd et al 1996, relatively large ejaculate volumes and epididymal sperm stores, large testicular size and ejaculated sperm concentrations, and production of large, firm copulatory plugs (Tyndale-Biscoe & Renfree 1987, Paris 2004. These plugs may enhance reproductive success by increasing sperm retention in the female tract, by locating spermatozoa in close apposition to the cervix and improving sperm transport into the cervix and uterus, and/or by acting as temporary barriers (chastity enhancement) to sperm deposition by other males (Murie & McLean 1980, Michener 1984, Toner et al 1987, Cukierski et al 1991a, 1991b, Taggart & Shimmin 1999, Jia et al 2002, although evidence in some species does not support chastity enhancement (Koprowski 1992, Moreira & Birkhead 2004. Success of these measures usually depend on a large ratio of testis to body weight, which in the tammar is around 0.5% (unpublished data of R V Short in Tyndale-Biscoe & Renfree 1987, Rose 1997, Taggart et al 1998, and is similar to that found in 31 multimating mammals (Kenagy & Trombulak 1986).…”
Section: Introductionmentioning
confidence: 99%